Asuhan Keperawatan Pada An. A dengan Penyakit Jantung Bawaan: Paten Duktus Arteriosus (PDA) di Ruang Melati II Rumah Sakit Umum Daerah Dr Moewardi Surakarta - Puspitasari, Linda; , Siti Arifah, S.Kp., M.Kes (2013)
Background of Study: Congenital heart disease is an abnormality of structure or function of the cardiovascular system were found at birth, although it can found in the next day. It can be caused due to lack of knowledge of parents, low education, and a supportive environment. Goal: To know the nursing care in patients with Patent ductus arteriosus include assessment, intervention, implementation and evaluation of nursing. Results: After the 3x24 hour nursing care available during coughing spasms and has not diminished, increased appetite, and yet showed excessive activity. Conclusion: Based on the results of the physical examination assessment data lungs are retracted, auscultation of breath sounds: Ronchi wet rough, pigeon chest shape chest, cardiac examination obtained thrill at apex, heart suit limits evaluated, and there are noisy systolic grade III / VI of the median II linea of the steralis sinistra.